Terrestrial arthropod faunal diversity in mangrove forest of North East Kolambugan, Lanao del Norte - Hanafi, Dearlee P. (CMU Graduate Journal, 2017)
The study was conducted in the mangrove forest of North East Kolambugan, Lanao del Norte from February 2012 to January 2013 to assess the existing terrestrial arthropod faunal diversity in the mangrove forest of Both East Kolambugan, Lanao del Norte. Specifically it aimed to: identify the present terrestrial arthropod species in the mangrove forest; determine the species richness of terrestrial arthropods in the mangrove forest; determine the diversity of terrestrial arthropod species in the mangrove forest; assert the terrestrial arthropods associations in the mangrove forest; determine the month of high abundance of terrestrial arthropods in the mangrove forest and determine the socio-economic factors of the respondents and their perception on the diversity of terrestrial arthropods in the mangrove forest of North East Kolambugan, Lanao del Norte. Sampling techniques namely: sweep net sampling, potato trap, beat sheet, water pan trap, sugar water trap and light trap were used in collecting terrestrial anthropods within five 10 x 10m sampling plots established in the mangrove forest. Structured questionnaires were administered to randomly selected respondents from the two barangays who lived near the vicinity of mangrove forest. There are 154 species of terrestrial anthropods in mangrove forest representing five Classes namely Arachnida, Collembola, Malacostraca, Chilopoda and Insecta. Among the five classes, Class insecta got the highest bulk of species which represented by thirteen orders namely Orthoptera, Blattodea, Hymenoptera, Lepidoptera, Diptera, Coleoptera, Thysanoptera, Hemiptera, Isoptera, Psocoptera, Dermaptera, Mantodea and Odonata. Coleoptera ranked first among the 13 Orders with 18.18% followed by Hymenoptera (17.53%), Diptera (14.28%), Hemiptera (10.39%), Lepidopteria (7.79%), Orthoptera (4.54%), Blattodea (1.54%), Odonata (1.30%) and 0.65% each for Psocoptera, Thysanoptera, Mantodea, Isoptera, and Dermaptera. Recorded associations of terrestrial anthropods in mangrove forest include predaceous, pollinators, phytophagous, parasitoids and scavengers/fungivorous, xyloborous. Phytophagous got the highest proportion of 37.01% among the associations present, followed by predaceous with 35.06%, scavengers/fungivorous 17.53%, parasitoids 5.2%, and both xyloborous and pollinators with 2.60%. It was observed in year round sampling, the highest bulk of species of terrestrial arthropods were collected during the month of June. The greater number of species of terrestrial arthropods were collected in sampling plots located in a more likely natural occurring state and undisturbed area with heavy mangrove vegetation. Protection, preservation and possible expansion of these areas are recommended as it is observed that lesser number of species were collected in plots located in areas which were usually disturbed by wind, level of tide and human activities.